2022
DOI: 10.3390/su14095081
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation and Organizational Performance of Online Business in Malaysia: The Mediating Role of the Knowledge Management Process

Abstract: The aim of this paper is to examine the role of the knowledge management process as a mediating variable in the relationship between entrepreneurial orientation and organizational performance. This study employed a quantitative method and utilised a self-administered questionnaire. A total of 350 data were collected from the owners/founders of online businesses. A Partial Least Squares-Structural Equation Modelling (PLS-SEM) analysis was performed to test the proposed hypotheses of the study. The findings indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 95 publications
(125 reference statements)
3
18
1
Order By: Relevance
“…The relationship between entrepreneurship orientation and innovation performance has been studied by a number of authors over the years (Adam, Fuzi et al, 2022;Beltrame, Grassetti et al, 2022), and as a result, various theoretical models, including the Organizational Theory of Innovation (Sehnem, de Queiroz et al, 2022) and the Schumpeterian Theory of Innovation (Callegari & Nybakk, 2022), have been found. These models serve as the foundations for innovation performance and organizational strategic management.…”
Section: Literature Review and Related Theoretical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between entrepreneurship orientation and innovation performance has been studied by a number of authors over the years (Adam, Fuzi et al, 2022;Beltrame, Grassetti et al, 2022), and as a result, various theoretical models, including the Organizational Theory of Innovation (Sehnem, de Queiroz et al, 2022) and the Schumpeterian Theory of Innovation (Callegari & Nybakk, 2022), have been found. These models serve as the foundations for innovation performance and organizational strategic management.…”
Section: Literature Review and Related Theoretical Basismentioning
confidence: 99%
“…Several studies examining the connection between entrepreneurial Orientation and organizational success have produced substantial results in association with business growth and performance (Clement, Huaicheo et al, 2021;Adam, Fuzi et al, 2022;Mintah, Gabir et al, 2022). Most discoveries from such studies have found a substantial and favourable entrepreneurial orientation-innovation nexus.…”
Section: Literature Review and Related Theoretical Basismentioning
confidence: 99%
“…In this line, EO is essential for inspiring and motivating workers to contribute their expertise and skills to the process of constructing knowledge (Lumpkin and Dess, 1996), and because knowledge plays such a big part in finding new opportunities and ideas, it needs to be managed correctly. Several previous studies proved the significant impacts of EO on KM in the case of building strategic alliances (Gupta and Moesel, 2007), leveraging individuals knowledge in the organization (Omotayo, 2015), a direct impact of EO on KM for SMEs in Southern Brazil (Severo et al, 2018), and significant influence of EO on KM for the SMEs in Iran (Madhoushi et al, 2011) and Online business in Malaysia (Adam et al, 2022). Based on the above discussions, the following hypothesis is proposed:…”
Section: Geo and Km Relationshipmentioning
confidence: 93%
“…The number of samples used in this study included 333 MSMEs, which have been included in the minimum sample number, according to Hair [50], and are in-between 5-10 of the indicator. The research used Structural Equation Modeling (SEM) analysis because it can test research hypotheses [32] using software analysis. The SEM model was developed from 2 analyses: the measurement and structural models.…”
Section: Data Collection and Samplingmentioning
confidence: 99%